The Role and Jurisdiction of Qadi in Islamic Law: Authority, Functions, and Contemporary Perspectives - Khan, Shahsawar (Al-Amīr Research Journal for Islamic Studies, 2024)
This research aims to study extensively the duties and role of Qadi (Judge) assigned by Shariah while performing under the organizational framework of the judiciary, whether being litigation in dispute between two private parties or adjudicating matters relating to the state. The legal term "Qadi," is derived from the Arabic word "Qada/Qaza" which refers to a judicial authority responsible for resolving conflicts. It will explore the domain of formal conventional adjudication to alternative dispute resolution with the jurisdiction of different Qadi’s i.e., from Qadi Aam to Qadi Madhaalim. It will showcase how the judicial system handled everything from family matters to Hudud punishments and from Hisbah oversight to issuing binding fatwas with its development during Abbasid era. Keywords: Jurisdiction Of Qadi, Islamic Judicial System, Role Of Judge In Islamic Law, Appeal Against Judgment In Islam, Judicial Authority, Alternative Dispute Resolution (ADR) in Islamic law